Highly anisotropic suspended planar-array chips with multidimensional sub-micrometric biomolecular patterns - Agusil, Juan Pablo; Torras, Núria; Duch, Marta; Esteve, Jaume; Pérez-García, Lluïsa; Samitier, Josep; Plaza, José A. (Wiley, 2017)
Suspended planar-array (SPA) chips embody millions of individual miniaturized arrays to work in extremely small volumes. Here, the basis of a robust methodology for the fabrication of SPA silicon chips with on-demand physical and chemical anisotropies is demonstrated. Specifically, physical traits are defined during the fabrication process with special focus on the aspect ratio, branching, faceting, and size gradient of the final chips. Additionally, the chemical attributes augment the functionality of the chips with the inclusion of complete coverage or patterns of selected biomolecules on the surface of the chips with contact printing techniques, offering an extremely high versatility, not only with the choice of the pattern shape and distribution but also in the choice of biomolecular inks to pattern. This approach increases the miniaturization of printed arrays in 3D structures by two orders of magnitude compared to those previously demonstrated. Finally, functional micro-metric and sub-micrometric patterned features are demonstrated with an antibody binding assay with the recognition of the printed spots with labeled antibodies from solution. The selective addition of physical and chemical attributes on the suspended chips represents the basis for future biomedical assays performed within extremely small volumes.